Anterior Interhemispheric Approach for Olfactory Groove Meningioma - Imam Hidayat; Agung Budi Sutiono; Ahmad Faried; Muhammad Zafrullah Arifin (International Journal of Integrated Health Sciences, 2016)
Objective: To evaluate the surgical technique with bifrontal interhemispheric approach for total removal of tumor in olfactory groove meningioma (OGM). Methods: This study described a case of a 38-year-old woman with bilateral blindness, anosmia, and behaviour changes. Imaging studies show a tumor mass in midfrontal base. Surgery using a bifrontal interhemispheric approach was performed and total removal was achieved and postoperative computed tomography (CT) scan was performed to confirm the result. Histopathological findings established a diagnosis of meningioma.Results: A coronal skin incision behind the hairline was utilized. The scalp was elevated, taking care to reserve the vascularized pericranium medial to the linea temporalis of each side, and preserving the 2 supraorbital nerves. Eight burr holes were used, with the two initial holes made on each side of the orbitotemporal region, and the other four holes at the midline. A bifrontal craniotomy was performed. The tumor was first detached from its attachment with bipolar cautery and debulked. During this step, the main tumor feeder arteries from the anterior and posterior ethmoidal artery were interrupted, and the tumor devascularized. Total tumor removal through surgical intervention was achieved and confirmed by head CT-scan postoperatively.Conclusions: This case report supports the suitability of the bifrontal interhemispheric approach for OGM resection with additional radiation therapy.Keywords: Anterior interhemispheric approach, olfactory groove meningioma DOI: 10.15850/ijihs.v4n2.838